Truth Tables of Considerations and Operations on Them - ugli, Yuldoshev Mansur Najmiddin (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article, one of the mathematical properties, reasoning, and the truth tables of operations on them are described in detail.